Analysis of bacterial diversity and functional differences of Jiang-flavored Daqu produced in different seasons - Wang, Lamei; Cheng, Yuxin; Hu, Xiaoxia; Huang, Yongguang (Frontiers in Nutrition, 2023)
High-temperature Daqu is an important saccharifying fermenting starter for brewing Jiang-flavored Baijiu. This paper analyzed the succession pattern of bacterial communities of Jiang-flavored Daqu (JFDQ) with seasonal changes through Illumina HiSeq sequencing and multivariate statistical methods. Results showed that 21 phyla, 529 genera, and 47 core bacterial genera were identified from the 48 composite samples. Among them, eight functional genera were only found in the summer-produced Daqu, including Propionigenium which can be fermented and metabolized to produce propionic acid and make the Baijiu softer. Besides, Pantoea, Bacillus, Lentibacillus, and Oceanobacillus respectively served as the representative functional bacterial genera of the four seasons. Microbial community function prediction and differential metabolite pathway enrichment analysis revealed the functional differences of Daqu samples produced in different seasons, especially related to glycolysis, acetoin biosynthesis, and ethanol fermentation. The functional microorganisms community in this paper would provide valuable suggestions about the seasonal production of JFDQ, guiding the Baijiu brewing processes.